The John–Nirenberg Inequality for the Regularized BLO Space on Non-homogeneous Metric Measure Spaces. Issue 3 (10th September 2020) - Lin, Haibo; Liu, Zhen; Wang, Chenyan
Abstract: Let (X, d, [STIX]x1D707) be a metric measure space satisfying the geometrically doubling condition and the upper doubling condition. In this paper, the authors establish the John-Nirenberg inequality for the regularized BLO space RBLO([STIX]x1D707) .